Studi Keanekaragaman Spermatophyta di Perbukitan Daerah Tlogodlingo Kecamatan Tawangmangu Kabupaten Karanganyar - Ima Aryani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The purpose of this study was to inventarize (1) an inventory species of Spermatophyte and (2) determine theindex of diversity and dominance of Spermatophyte species of hills Tlogodlingo area. This study is a descriptiveeksplorasif study conducted Tlogodlingo in Tawangmangu District of Karanganyar. The population in thisstudy is all types of plants in the hills Tlogodlingo. Sample in this research is type spermatophyta in hilly ofTlogodlingo. Determination of place as the location of sampling is done by purposive sampling. Sampling datais taken on each observation using method of quadratic sampling. The results showed that there are 12 speciesof plants Spermatophyta, namely Acacia decurrens, Ficus firtulosa, Melastoma malabathricum, Eupatoriumodoratum, Ageratum conyzoides, Imperata cyliandrica, Lantana camara, Polygala paniculata, Eupatoriumriparium, Borreria alata, Emilia sonchifolia, and Synedrella nodiflora. The value of diversity index ofSpermatophytes obtained in is 0.686 that means the diversity is low at hilly Tlogodlingo. The highestdominance index was Imperata cyliandrica and the lowest dominance index was Synedrella nodiflora..